Evaluation of Experimental Proximal Femoral Physeal Fractures Repaired with Two Cortical Screws Placed from the Articular Surface - Tillson, D. M.; McLaughlin, R. M.; Roush, J. K. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Proximal femoral physeal fractures were surgically created unilaterally in twelve immature dogs and repaired using two cortical screws placed in lag fashion from the articular surface into the femoral neck. Four dogs were euthanatized at two, four and eight weeks after surgery and evaluated by gross examination, fine detail radiography, fine detail angiography and histology. Mild to severe injury to the articular cartilage of the acetabulum was observed in all operated joints. Narrowing of the femoral neck was evident on fine detail radiographs and was most severe at week four. Metaphyseal vessels crossed the physis and revascularized the epiphysis with greater than 90% of the epiphysis being revascularized by eight weeks. Operated femora showed histological evidence of physeal disruption and premature physeal closure. Osteocyte death in the epiphysis was evident histologically with viable osteocytes following revascularization and proceeding from distal to proximal through the epiphysis over eight weeks.The healing of proximal fe-moral physeal fractures repaired with two, 2.0 mm cortical screws placed from the articular surface was evaluated by gross evaluation, fine detail radio-graphs and angiographs, and histological examination. Fracture healing and restoration of blood supply was adequate for weight bearing. This technique is acceptable for use in clinical patients.
Keywords: Proximal femur; physeal fracture; blood supply; physis; dogs